母子福利基金会中专一年级学生应用PLECO汉语词典软件情况 分析 - Zainul MUSTAFA; Lily Thamrin; Lusi Lusi (Journal International Lingua Mandarin (JILIN), 2022)
The purpose of this article is to understand the students' application of PLECO Chinese dictionary software; analyze the advantages and disadvantages of students' application of PLECO Chinese dictionary software. The author's research object is a total of 124 students in the first grade of secondary school of the Mother and Child Welfare Foundation. This research uses quantitative research, and the research tools used are questionnaire method and test method. The results of the study show that students' use of PLECO Chinese dictionary software has reached a moderate level, indicating that students are more familiar with using PLECO Chinese dictionary software. The students expressed their satisfaction with the PLECO Chinese dictionary software. Most of the students think that using the PLECO Chinese dictionary software will get a lot of help, and the comparison results of the before and after tests show that the students' scores have improved. But the students also said that there are still some problems with the software, such as only English explanations and no Indonesian explanations.